The Politicization of the European Union From Processes to Consequences - Bolzonar, Fabio (European Studies, 2023)
What are the consequences of EU politicization for the EU and European societies? This book shifts the analytical focus from EU politicization processes to their empirical and normative research on the effects of politicization on public opinion, public discourses, policymaking and European integration.